2020
DOI: 10.1002/ppul.25004
|View full text |Cite
|
Sign up to set email alerts
|

Persistent tachypnea of infancy: Follow up at school age

Abstract: Background: Persistent tachypnea of infancy (PTI) is a rare pediatric lung disease of unknown origin. The diagnosis can be made by clinical presentation and chest high resolution computed tomography after exclusion of other causes. Clinical courses beyond infancy have rarely been assessed. Methods: Patients included in the Kids Lung Register diagnosed with PTI as infants and now older than 5 years were identified. Initial presentation, extrapulmonary comorbidities, spirometry and clinical outcome were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…At present, there is limited information about the evolution of lung function during the following years 3,14 . Recently Seidl et al reported normal spirometry in children with NEHI between 5 and 10 years old 13 . It is possible that lung function improves over longer periods of time, although more sensitive techniques such as multiple breath wash out, may demonstrate pulmonary function abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there is limited information about the evolution of lung function during the following years 3,14 . Recently Seidl et al reported normal spirometry in children with NEHI between 5 and 10 years old 13 . It is possible that lung function improves over longer periods of time, although more sensitive techniques such as multiple breath wash out, may demonstrate pulmonary function abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually present with frequent respiratory exacerbations, poor weight gain, sleep‐related breathing disorders and the need for supplemental oxygen therapy 10–12 . Although clinical course is generally favorable, the long‐term outcome has not yet been fully established 7,13 . To date, there are no reports available about this entity in our country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of PTI children at school age used ICS. 15 However, to date, no highquality studies to assess the effectiveness of any kind of treatment in children with PTI have been conducted.…”
Section: Pftsmentioning
confidence: 99%
“…5,14 The clinical course of PTI is mostly mild or moderate, and affected children gradually improve during childhood. 15 However, some patients require oxygen supplementation for a longer time 11,16 and sometimes symptoms may persist until adulthood. 16,17 Data on pulmonary function tests (PFTs) in children with PTI are sparse.…”
mentioning
confidence: 99%